Estudo comparativo de tecnologias para o desenvolvimento de API's de geolocalização - Luft, Gustavo Alberto (2025)
This paper presents a comparative study of different back-end technologies for the development of geolocation APIs, focusing on performance, usability, and support for handling geospatial data. The rationale for this research is based on the growing need for systems to handle large volumes of georeferenced data. The study aimed to evaluate specialized libraries and frameworks, analyze the performance of APIs developed in Java, JavaScript, and Python, and conduct comparative tests to identify the advantages and limitations of each technology. The methodology involved the implementation of three APIs following the REST architecture, conducting performance and stress tests, and analyzing integration with the front-end. The research contributes to the field of API development and geospatial data handling by providing a comparative foundation for future implementations and technological improvements. Future studies may expand on this analysis by exploring new technologies and approaches for performance optimization.